2019
DOI: 10.7784/rbtur.v13i3.1582
|View full text |Cite
|
Sign up to set email alerts
|

Mexico and Uruguay inbound tourism demand

Abstract: The main objective of this paper is to estimate the tourism demand for Mexico and Uruguay, two very different countries, but for both of which tourism is an important activity, and mainly originating from a large neighbor. We try to analyze whether the determinants of tourism demand differ depending on the size of the country, or if being a neighboring country is the main determinant. So, we analyze the relationship between the number of American tourists visiting Mexico and Argenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…In addition, cattle raising in Uruguay is mainly based on grass feeding, whose quality depends on weather conditions (Baethgen, ). Regarding tourism, it represents about 4% of the gross domestic product and generates 6% of the total employment (Mordecki, ). The main characteristic of this activity is that it has a strong seasonality, because it is centred around the beach (which is located in the south) and in the summer season (Brida et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cattle raising in Uruguay is mainly based on grass feeding, whose quality depends on weather conditions (Baethgen, ). Regarding tourism, it represents about 4% of the gross domestic product and generates 6% of the total employment (Mordecki, ). The main characteristic of this activity is that it has a strong seasonality, because it is centred around the beach (which is located in the south) and in the summer season (Brida et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This practice has positive consequences for the whole region and provides various benefits. A study by Mordecki et al (2019) found that tourism demand in Mexico and Uruguay is influenced by an important border country. This underlines the importance of neighboring countries in attracting tourists and enhancing tourism efforts.…”
Section: Being a Neighboring Country For Tourism Industrymentioning
confidence: 99%
“…Jika dilihat dari media yang digunakan, bullying dibagi menjadi dua tipe, yakni tipe cyber bullying dan tipe tradisional bullying. Cyberbullying seperti tindakan pelecehan dan aniaya dapat terlaksana dengan menggunakan bantuan media sosial, artinya tindakan tersebut dilakukan melalui perantara media sosial (Mordecki, 2014). Sarwono (2012) mengatakan jika adolescence merupakan kata latin dari remaja yang memiliki arti berkembang dari segi kematangan psikis, fisik, dan sosial.…”
Section: Bhakti Nagori (Jurnal Pengabdian Kepada Masyarakat)unclassified